Statins decrease overall mortality and cancer related mortality but are underutilized in NAFLD: a longitudinal analysis of 12, 538 individuals. (2nd September 2022) - Ng, Cheng Han; Teng, Margaret LP; Chew, Nicholas WS; Chan, Kai En; Yong, Jie Ning; Quek, Jingxuan; Tan, Darren Jun Hao; Lim, Wen Hui; Lee, Gabriel Sheng Jie; Wong, Jessica; Kaewdech, Apichat; Huang, Daniel Q; et al.
ABSTRACT: Background: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease. NAFLD is associated with dyslipidemia, and cardiovascular mortality remains the leading cause of death. While statins are the first-line therapy in hyperlipidemia, their utilization has been suboptimal. Hence, we examined the use of statins in NAFLD and mortality. Research design and methods: Analysis was performed with the National Health and Nutrition Examination Survey (NHANES) data from 1999 to 2018. Longitudinal outcomes were assessed with survival analysis. Results: Of 12, 538 NAFLD patients, 6, 452 were indicated for hyperlipidemia treatment. Statin usage was highest among high-risk individuals (44.28%) and lowest among low-risk individuals (8.48%). The risk of overall (HR: 0.87, CI: 0.76 to 0.99, p = 0.04) and cancer-related (SHR: 0.73, CI: 0.54 to 0.99, p = 0.04) mortality was significantly lower in NAFLD patients with statins. There was no significant decrease in cardiovascular-related mortality. Conclusion: Over concerns of hepatotoxicity and lack of evidence in reducing mortality events, statins remain underutilized in NAFLD. However, statin use was associated with a significant reduction in overall and cancer-related mortality. The lack of reduction in cardiovascular disease mortality is likely a selection bias of patients, where individuals with higher risk are more likely to receive treatment.